Elementary mathematics reseach done by primary school pupils - Kiseliovas, Arkadijus; Kiseliova, Danutė (Lietuvos matematikos rinkinys, 1999)
The problem of the elementary mathematics research done by primary school pupils has been discussed. Elementary mathematics research is performed according to the new set of teaching devices "In The World of Mathematics" meant for the primary school.